Enhancing Numeracy Skills through Realistic Mathematics Education: A School-Based Study at Sekolah Kebangsaan Seri Suria - Ahmad Farid Rahman; Nur Aisyah Zulkifli (Journal of Science and Mathematics Education, 2026)
This study aims to examine the effectiveness of the Realistic Mathematics Education (RME) approach in enhancing students’ numeracy skills at Sekolah Kebangsaan Seri Suria. Numeracy is a fundamental competence that supports students’ ability to apply mathematical concepts in real-life contexts; however, many primary school students experience difficulties in connecting abstract mathematical ideas to everyday situations. To address this issue, a quasi-experimental design with a pre-test and post-test control group was employed. The participants consisted of 60 Year 5 students divided into an experimental group receiving instruction through the RME approach and a control group taught using conventional methods. Data were collected through standardized numeracy tests and classroom observation sheets. The results indicated a statistically significant improvement in the experimental group’s post-test scores compared to the control group. Students exposed to RME demonstrated better conceptual understanding, problem-solving abilities, and engagement during learning activities. The findings suggest that contextual learning tasks, student-centered exploration, and guided reinvention processes embedded in the RME framework contribute positively to numeracy development. This study highlights the importance of integrating realistic contexts into mathematics instruction to foster meaningful learning experiences. It is recommended that primary school teachers adopt RME strategies to strengthen numeracy proficiency and promote deeper mathematical understanding among learners.